Making Journalism and Artificial Intelligence: uses of GPT Chat in news production - Sabino, Vinicius Jose Biazotti [UNESP]; Colombo, Macri Elaine; Varela, Ulysses do Nascimento (Univ Estadual Paulista Julio Mesquita Filho, Fac Arquitetura Artes & Comun, 2024)
This article aims to discuss how advanced artificial intelligence, such as Chat GPT, can interfere in the way journalistic texts are produced. Methodologically based on an experiment that aims to discuss how the tool can limit or assist the work of textual reporters, mainly on the issue of their professional ethos, involving their commitment to the veracity of the facts and their relationship with the sources. For theoretical discussion, the article uses references about journalism in the era of artificial intelligence, debates about journalistic ethics and also discusses the mode of professional production. Furthermore, based on the results obtained, it proposes a question about how the tool can interfere in the performance of daily journalistic processes.
Keywords: Artificial Intelligence; GTP Chat; Journalism